Validity and Regulatory and Legal Basis of Selection in the Training of Football Players (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This study examines the validity of various selection methods used by coaches, scouts, and academies to identify talent, ensuring that these methods are not only effective but also scientifically supported. Furthermore, it delves into the regulatory and legal aspects governing player selection, including policies established by football associations, labor laws, and ethical guidelines that protect players' rights, particularly minors, in the selection and training process. The research addresses the balance between achieving optimal player development and adhering to legal standards, ensuring fairness and non-discrimination in selection practices. Through this analysis, the study aims to highlight the importance of transparency, fairness, and consistency in player selection, alongside the legal obligations to protect the welfare of young athletes in the global football ecosystem.